2010
DOI: 10.2478/s11686-010-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Diploproctodaeum spp. (Digenea, Lepocreadiidae) in Australian and New Caledonian waters including two new species from Tetraodontiformes and new records of related species

Abstract: Diploproctodaeum monstrosum sp. nov. is described from Arothron stellatus and A. mappa from off Lizard Island, northern Great Barrier Reef. It differs from its congeners in having a body-length ventral scoop. Diploproctodaeum triodoni sp. nov. is described from Triodon macropterus off New Caledonia. It is distinguished by the extensive vitelline fields usually reaching to the ventral sucker and the folded scoop margins. Other related species are reported from new hosts or localities and dimensions are supplied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…These authors pointed out the similarity of these worms to those described from L. lunaris by Hafeezullah ( 1970 ) under the name B. plicitum (Linton, 1928) from off Chennai (as Madras) in the Bay of Bengal and by Shen & Tong ( 1990 ) under the name B. dayawanense Shen & Tong, 1990 from Daya Bay, China [in this case the host is quoted as L. lunaris spadiceus (Richardson)]. The lateral flanges of the Bay of Bengal worms are similar to those seen in our specimens and the dimensions are close to those found by Sey ( 1996 ) and Bray et al ( 2010a ) (Supplementary Table S1). The Chinese worms tend to be larger and the flanges are illustrated as distinct flaps reaching only to the ventral sucker level.…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…These authors pointed out the similarity of these worms to those described from L. lunaris by Hafeezullah ( 1970 ) under the name B. plicitum (Linton, 1928) from off Chennai (as Madras) in the Bay of Bengal and by Shen & Tong ( 1990 ) under the name B. dayawanense Shen & Tong, 1990 from Daya Bay, China [in this case the host is quoted as L. lunaris spadiceus (Richardson)]. The lateral flanges of the Bay of Bengal worms are similar to those seen in our specimens and the dimensions are close to those found by Sey ( 1996 ) and Bray et al ( 2010a ) (Supplementary Table S1). The Chinese worms tend to be larger and the flanges are illustrated as distinct flaps reaching only to the ventral sucker level.…”
Section: Methodssupporting
confidence: 87%
“…Bray et al ( 2010a ) reported this species in Arothron stellatus and A. mappa from off Lizard Island. They pointed out that the sequence of ‘ Diploproctodaeum sp.’ from A. stellatus off Lizard Island (GenBank FJ788474), used in the study of Bray et al ( 2009 ), referred to this species.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Members of the digenean family Lepocreadiidae Odhner, 1905 are common parasites of fishes of the Indo-West Pacific region, particularly of coral reef fishes. Our systematic studies on this family in the waters around northern Australia and other sites in the region have hitherto been mostly reliant on comparative morphology (Barker et al, 1993 ; Bray et al, 1993 ; Bray & Cribb, 1996a , b , c , d ; Bray et al, 1996a , b ; Bray & Cribb, 1998 ; Bray et al, 1998 ; Bray & Nahhas, 1998 ; Bray & Cribb, 2002 , 2003 ; Bray & Justine, 2006 ; Bray et al, 2009a , b ; Bray et al, 2010a , b ; Bray & Justine, 2012 ). More recently, some progress has been made in our understanding of higher level lepocreadiid systematics (Bray et al, 2009b ; Bray & Cribb, 2012 ; Bray et al, 2018 ) by the addition of molecular evidence.…”
Section: Introductionmentioning
confidence: 99%